Innovation in the Use of Rigid Pavement Waste in Recycled Concrete: Challenges and Solutions to Improve Mechanical Performance - Lubab, Lubab; Antonius, Antonius; Sumirin, Sumirin (ASTONJADRO, 2025)
The use of rigid pavement waste as recycled aggregate in concrete has become a focus of research in an effort to improve sustainability in the construction industry. This article discusses the main challenges in using rigid pavement waste as recycled aggregate, especially related to the mechanical strength of concrete, such as compressive and flexural strength. In addition, this article also explores various innovations in concrete mix design that can overcome the mechanical performance weaknesses of recycled concrete. Some of the solutions discussed include the use of reinforcing fibers, alternative binders, and more efficient production technologies. The research shows that these innovations can significantly improve the performance of recycled concrete with rigid pavement waste aggregate, making it a viable option to support more environmentally friendly infrastructure development.